G199(P) Use of Fish-Oil Based Intravenous Lipid Emulsion as a Rescue in Infants with Intestinal Failure-Associated Liver Disease Who Develop Sepsis. (4th June 2013) - Lee, HM; Hickey, A; O'Meara, M; Thompson, L; Hind, J
Abstract : Aims: In infants with intestinal failure-associated liver disease (IFALD), it is known that episodes of sepsis can be accompanied by a significant deterioration in liver function. We hypothesised that an intravenous lipid emulsion (ILE) comprised solely of fish oil, high in omega-3 fatty acids, such as Omegaven ®, may protect the liver in these infants during episodes of sepsis. Our aim is to describe the potential role for Omegaven ® as a rescue therapy in infants with sepsis and established IFALD. Methods: A mixed source ILE containing both omega-3 and omega-6 fatty acids (SMOFlipid ® ) was used as first-line in infants at high risk of IFALD. When infants with IFALD developed sepsis, Omegaven ® was used as the sole ILE for up to 14 days. A retrospective review of their case notes was conducted. Results: Omegaven ® was well tolerated in all infants. 7 infants had Omegaven ® treatment during a 14-month period (August 2011-October 2012). Median birth weight was 1000g (range 527–1870). Median gestation at birth was 30 weeks (range 24–34). Of the 7 patients, 2 had gastrochisis and 5 had necrotising enterocolitis (NEC). One patient with gastrochisis developed NEC. 2 patients were late transfers at 4–5 months of age from other hospitals with severe and progressive IFALD. Both subsequently died. Median age at start of Omegaven ® was 63 days (range 7–189). 3 patients did not complete the full 2-week course of Omegaven ® . All had total bilirubin levels above 80μmol/l at commencement of Omegaven ® . During their episodes of sepsis, bilirubin and CRP rose in all patients. Transaminases were deranged in all. All 7 patients showed improvement in septic markers during Omegaven ® treatment. 3 patients showed improvement in bilirubin during treatment, which was maintained in the long term in 2. 1 patient was transferred to another centre for further medical treatment early in her Omegaven ® course: her bilirubin was static. Conclusion: Use of Omegaven ® as a short term rescue ILE in infants with IFALD and sepsis appears safe. The expected deterioration in liver function associated with sepsis was not seen in this series.